A Philosophical Examination of Social Justice and Child Poverty - Schweiger, G. (Springer Nature, 2015)
This book is open access under a CCBY license. This book investigates child poverty from a philosophical perspective. It identifies the injustices of child poverty, relates them to the well-being of children, and discusses who has a moral responsibility to secure social justice for children.